Adaptive Learning Frameworks for Islamic-Based Character Education in Child-Friendly School Leadership - Titi Sartini; Nini; Hidayati Suhaili; Mona Novita; Raudlotul Hikmah (Journal of Educational Management Research, 2025)
This study aims to examine and formulate an adaptive learning framework in Islamic-based character education integrated with child-friendly school leadership. The primary focus lies on how Islamic values—including aqidah, sharia, and akhlakul karimah—are internalized through a learning approach that is responsive to the individual needs of students, and managed in a leadership climate that supports child protection and participation. This study employs a qualitative approach, utilizing a case study method at the madrasah. Data were collected through in-depth interviews, participant observation, and documentation studies. The results of the study show four main findings: (1) the foundation of Islamic values ​​as the moral framework of the institution; (2) an adaptive learning approach that adapts to students’ learning styles and backgrounds; (3) child-friendly leadership practices that foster a sense of security and active involvement of students; and (4) a holistic evaluation that assesses academic and character development in an integrative manner. This study recommends the development of an Islamic character-based adaptive learning model, supported by a participatory and inclusive leadership culture, within the school environment.